Physiological, Anatomical and Metabolic Implications of Salt Tolerance in the Halophyte Salvadora persica under Hydroponic Culture Condition - Parida, Asish K.; Veerabathini, Sairam K.; Kumari, Asha; Agarwal, Pradeep K. (Frontiers in Plant Science, 2016)
Salt tolerance mechanism of an extreme halophyte Salvadora persica was assessed by analysing growth, nutrient uptake, anatomical modifications and alterations in levels of some organic metabolites in seedlings imposed to various levels of salinity (0, 250, 500 and 750 mM NaCl) under hydroponic culture condition. After 21 days of salt treatment, plant height, leaf area and shoot biomass decreased with increase in salinity whereas the leaf succulence increased significantly with increasing salinity in S. persica. The RWC% of leaf increased progressively in salt-treated seedlings as compared to control. Na+ contents of leaf, stem and root increased in dose-dependent manner whereas there was no significant changes in K+ content. There was significant alterations in leaf, stem and root anatomy by salinity. The thickness of epidermis and spongy parenchyma of leaf increased in salt treated seedlings as compared to control, whereas palisade parenchyma decreased dramatically in extreme salinity (750 mM NaCl). There was a significant reduction in stomatal density and stomatal pore area of leaf with increasing salinity. Anatomical observations of stem showed that the epidermal cells diameter and thickness of cortex decreased by salinity whereas thickness of hypodermal layer, hypodermal cell diameter, pith area and pith cell diameter increased by high salinity. The root anatomy showed an increase in epidermal thickness by salinity whereas diameters of epidermal cells and xylem vessels decreased. Total soluble sugar content remained unchanged at all levels of salinity whereas reducing sugar content increased by 2-fold at high salinity (750 mM NaCl). The starch content of leaf decreased progressively in NaCl treated seedlings as compared to control. Total free amino acid content did not change at low salinity (250 mM), whereas it increased significantly at higher salinity (500 and 750 mM NaCl). The proline content increased in the NaCl treated seedlings as compared to control. There was no significant changes in polyphenol levels in leaf at all levels of salinity. The results from the present study reveal that seedlings imposed with various levels of salinity experience physiological, biochemical and anatomical modifications in order to circumvent under extreme saline environment. The vital mechanisms of salt tolerance in this